PENGARUH MANAJEMEN LABA, DAN KEPEMILIKAN MANAJERIAL PADA KESEJAHTERAAN PEMEGANG SAHAM PERUSAHAAN TARGET AKUISISI - SUKARTHA, I MADE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 1 (2008))
The main accounting issue in this research which can trigger wealth transfer from acquiring company’s shareholders to target company’s shareholders is earning management that was done during the last publication before the acquisition. Therefore, the purposes of this research are: (1) to test whether the target company’s management performed earnings management by increasing the amount of earnings which was reported in the last publication before the acquisition announcement, (2) to test whether the earnings management which was done by the target company benefit their shareholders, and (3) to test whether managerial ownership affects earnings management and the wealth of the target company’s shareholders. Hypotheses in this research were developed using agency theory as the main theory, which was supported by earnings management theory with the same motivations as this research such as bonus plan motivation, chief executive officer (CEO) change motivation, and Initial Public Offering (IPO) motivation, and Efficient Market Hypothesis. The sample for this research are target companies undergone successful acquisition in Jakarta Stock Exchange from 1990 to 2005. The sample consists of 54 target companies. The dependent variable of target companies shareholders’ wealth, is represented by cumulative abnormal return (CAR) as the proxy, calculated by using the Market Model. The independent variable of earnings management is calculated by Modified Jones Model, and the ownership managerial variable is calculated by management ownership percentage on target company’ shares. The research hypothesis is tested by t-test and ordinary least square regression test. The result of this research is: (1) the target company is doing earnings management by increasing discretionary accrual for the last publication just before the acquisition, (2) the positive effect of earnings management on target company shareholders wealth at the last publication just before the acquisition is bigger and more significant statistically compared with the previous period, and (3) managerial ownership has positive effect and statistically significant on target company shareholders’ wealth during the last publication just before the acquisition.
Keywords: Earning management, Wealth transfer, Acquiring company’s shareholders, Target company’s shareholders, Acquisition, Managerial ownership, Relative size of target company.